Proslavery and sectional thought in the early South, 1740-1829 : an anthology - Young, Jeffrey Robert (University of South Carolina Press, 2006)
Even then the theorists included in this anthology emphasized the extent to which southern slaveholders' claims to mastery were rooted in a Western moral tradition that reached back to antiquity.
Keywords: Slavery -- Southern States -- Justification -- Sources.; Southern States -- Intellectual life -- Sources.; Sectionalism (U.S.) -- History -- Sources.; Slavery and the church -- Southern States -- History -- Sources.; Racism -- Southern States -- History -- Sources.; Slavery -- Southern States -- History -- 18th century -- Sources.; Slavery -- Southern States -- History -- 19th century -- Sources.; Southern States -- Politics and government -- To 1775 -- Sources.; Southern States -- Politics and government -- 1775-1865 -- Sources.; Esclavage -- États-Unis (Sud) -- Justification -- Sources.; Racisme -- États-Unis (Sud) -- Histoire -- Sources.; États-Unis (Sud) -- Politique et gouvernement -- Jusqu'à 1775 -- Sources.; États-Unis (Sud) -- Politique et gouvernement -- 1775-1865 -- Sources.; SOCIAL SCIENCE -- Slavery.; Sectionalism (United States); Intellectual life; Politics and government; Racism; Slavery; Slavery and the church; Slavery -- Justification; Southern States; États-Unis (sud) -- Politique et gouvernement -- Histoire -- Sources.; Esclavage -- États-Unis -- Histoire -- Sources.; christianisme -- esclavagisme -- racisme -- regionalisme -- Etats-Unis -- sud -- 1740 -- 1829 -- document.; To 1899; History; Sources